Phytochemical and Biological Investigations of Saurauja roxburghii - Alim Uddin Chowdhury, Md.; Atiar Rahman, Md.; Zahan, Marufa; Hossain Sohrab, Md.; Md. Monirul Hasan, Chowdhury; Ahmed, Yunus (Asian Journal of Chemistry, 2011)
Two compounds were isolated from the n-hexane soluble fraction of a petroleum ether extract of the Saurauja roxburghii leaf. The structures of the isolated compounds were elucidated as b-amyrin (1) and stigmasterol (2), by high field NMR analyses as well as by comparison with structurally related compounds. In in vitro thrombolytic assay, 100 μL methanol extract of Saurauja roxburghii showed 26.09 % blood clot lytic activity. Promising antibacterial activity of Saurauja roxburghii extract against 4 gram positive and 6 gram negative bacteria were observed in disc diffusion technique. In in vitro antioxidant assay, both the extract and ascorbic acid (standard antioxidant) showed very good DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging activity with IC50 value 3.34 μg/mL for extract and 0.05 μg/mL for ascorbic acid.